Vitamin D Level of Children with Diabetic Ketoacidosis in Pediatric Intensive Care Unit - Semra Çetinkaya; Şenay Savaş Erdeve; Erhan Ozel; Mutlu Uysal Yazici; Emine Gulsah Torun (Genel Tıp Dergisi)
Aims: Vitamin D deficiency is a risk factor for autoimmune diseases such as diabetes mellitus. This study aimed to investigate the association between Diabetic ketoacidosis (DKA) and vitamin D levels and the impact of vitamin D on the duration of DKA and pediatric intensive care unit length of stay in Turkish pediatric patients. Methods: The study was a retrospective study conducted between January 2014 and March 2018. The study population was children under 18 admitted to the pediatric intensive care unit (PICU) with DKA. Results: The study included 130 patients, 51.5% of them were females. We found vitamin D deficiency in 39.2%(n=51) and vitamin D insufficiency in 33.1% (n=43) of the patients. Most of the patients with severe acidosis had low vitamin D levels (44/59) and % 45.8 of them (27/59) had vitamin D deficiency. Duration of diabetic ketoacidosis, length of pediatric intensive care unit stay, and hospitalization stay were longer in patients with low vitamin D levels but were not statistically significant. Conclusions: This study is the first study evaluating the association between vitamin D and diabetic ketoacidosis in Turkey. Although there is no association between vitamin D deficiency and the duration of diabetic ketoacidosis and the severity of acidosis, vitamin D deficiency is substantially common in patients with diabetic ketoacidosis.